Effect of bodychecking on rate of injuries among minor hockey players - Cusimano, Michael D (Open Medicine Publications, Inc., 2011)
BACKGROUND: Bodychecking is a leading cause of injury among minor hockey players. Its value has been the subject of heated debate since Hockey Canada introduced bodychecking for competitive players as young as 9 years in the 1998/1999 season. Our goal was to determine whether lowering the legal age of bodychecking from 11 to 9 years affected the numbers of all hockey-related injuries and of those specifically related to bodychecking among minor hockey players in Ontario. METHODS: In this retrospective study, we evaluated data collected through the Canadian Hospitals Injury Reporting and Prevention Program. The study’s participants were male hockey league players aged 6–17 years who visited the emergency departments of 5 hospitals in Ontario for hockey-related injuries during 10 hockey seasons (September 1994 to May 2004). Injuries were classified as bodychecking-related or non-bodychecking-related. Injuries that occurred after the rule change took effect were compared with those that occurred before the rule’s introduction. RESULTS: During the study period, a total of 8552 hockey-related injuries were reported, 4460 (52.2%) of which were attributable to bodychecking. The odds ratio (OR) of a visit to the emergency department because of a bodychecking-related injury increased after the rule change (OR 1.26, 95% confidence interval [CI] 1.16–1.38), the head and neck (OR 1.52, 95% CI 1.26–1.84) and the shoulder and arm (OR 1.18, 95% CI 1.04–1.35) being the body parts with the most substantial increases in injury rate. The OR of an emergency visit because of concussion increased significantly in the Atom division after the rule change, which allowed bodychecking in the Atom division. After the rule change, the odds of a bodychecking-related injury was significantly higher in the Atom division (OR 2.20, 95% CI 1.70–2.84). INTERPRETATION: In this study, the odds of injury increased with decreasing age of exposure to bodychecking. These findings add to the growing evidence that bodychecking holds greater risk than benefit for youth and support widespread calls to ban this practice.